DINAMIKA COPING STRESS PASCA BENCANA ALAM LIKUIFAKSI DI KOTA PALU - edwin edwin; Hardani Widhiastuti (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2023)
This study was conducted to determine the dynamics of coping with stress after thenatural liquefaction disaster in Palu. This incident happened for the first time inresidential areas in Palu, on September 28, 2018, which claimed many lives, so thatsurvivors experienced stress, and the stress-coping methods were also different. Thisresearch method uses qualitative by using a psychological phenomenology approach.While data analysis techniques are carried out in several stages: data reduction, datadisplay, and concluding/verification. The findings of this paper indicate that thedynamics of coping with stress experienced by survivors of the liquefaction naturaldisaster in Palu on September 29, 2018, are different or varied. But at the stage that theindividual leads to a gradual effort to reduce the stress experienced. In negative coping,individuals directly involved with the liquefaction natural disaster experience stress,confusion, shock, and a sense of wanting to die, after the disaster, there is still trauma.In positive coping, individuals directly involved with the natural liquefaction disasterappear to be trying to save themselves by running and looking for a way out until theyfinally survive. After the natural liquefaction disaster, individuals reduce their stress byworking, entertaining themselves by worshipping God, always gather with family as astrength that adds to the spirit, and always be grateful.